Semantic change in Portuguese: considering Cerrado and Vereda - Marraa, Daniel; Quinn, Marie; Blamires, Luiz Arthur (Penerbit Universiti Kebangsaan Malaysia, 2020)
This paper highlights the process by which meaning instantiates itself in word formation and discusses how semantic change installs subsequently in them, in this case, the Portuguese words cerrado and vereda. These two words have long individual histories that can be tracked back to their Latin or Celtic etymons, cerrado rooted in the origin of the Latin verb serāre, which gave origin to the Portuguese verb cerrar (to close, to seal) and vereda (narrow path) derived from the Latin word veredus (horse), which has its root in the Celtic word voredos. Yet, in the modern Brazilian context, Cerrado designates a particular ecosystem, the second largest biome in the country, that of short, closely-packed trees and foliage, and Vereda, a verdant subsystem of the same ecosystem. The discussion tracks the linguistic movement to arrive at these current meanings, showing how understanding the “history” of a word helps to understand both the uniqueness of its morpho-phonological and semantic constitution, as well as that of its relationship with the object it designates in the empirical world.